Mitochondrial Priming By CD28 - Klein Geltink, Ramon I. (Cell, 2017)
T cell receptor (TCR) signaling without CD28 can elicit primary effector T cells, but memory T cells generated during this process are anergic, failing to respond to secondary antigen exposure. We show that upon T cell activation, CD28 transiently promotes expression of carnitine palmitoyltransferase 1a (Cpt1a), an enzyme that facilitates mitochondrial FAO, before the first cell division, coinciding with mitochondrial elongation and enhanced spare respiratory capacity (SRC). microRNA-33 (miR33), a target of thioredoxin-interacting protein (TXNIP), attenuates Cpt1a expression in the absence of CD28, resulting in cells that thereafter are metabolically compromised during reactivation or periods of increased bioenergetic demand. Early CD28-dependent mitochondrial engagement is needed for T cells to remodel cristae, develop SRC, and rapidly produce cytokines upon restimulation – cardinal features of protective memory T cells. Our data show that initial CD28 signals during T cell activation prime mitochondria with latent metabolic capacity essential for future T cell responses.